2014
DOI: 10.1016/j.jalz.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admissions, outpatient visits and healthcare costs of community‐dwellers with Alzheimer's disease

Abstract: It would be important to assess whether inpatient hospitalizations of AD patients could be decreased by better targeting of outpatient services and whether other conditions are underdiagnosed or undertreated among persons with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 18 publications
2
28
1
1
Order By: Relevance
“…Furthermore, 1 study reported a 72% lower odds for PWD to have a LOS of 10 days or more compared to PwoD (95% CI: 0.1‐0.4) . With exception of 1 study conducted in Ireland, the remaining studies across Europe reported a longer LOS for PWD of up to 22 days . Within countries, the different studies were consistent in reporting a longer LOS for PWD compared to PwoD; however, the difference in the LOS varied up to 13 days …”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Furthermore, 1 study reported a 72% lower odds for PWD to have a LOS of 10 days or more compared to PwoD (95% CI: 0.1‐0.4) . With exception of 1 study conducted in Ireland, the remaining studies across Europe reported a longer LOS for PWD of up to 22 days . Within countries, the different studies were consistent in reporting a longer LOS for PWD compared to PwoD; however, the difference in the LOS varied up to 13 days …”
Section: Resultsmentioning
confidence: 93%
“…Eleven studies had a small sample size (range: 42‐395), were conducted in a single hospital (‐ward), or showed a sex distribution not representative of the PWD population . Thirty‐three studies met the criteria for comparability based on design or analysis, thereof 8 studies controlled or matched for 1 factor and 25 studies for at least 2 factors . Fourteen studies reported multivariate and descriptive results for LOS, and 5 studies solely multivariate results .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2014, a French study showed that the average total monthly costs of AD were €2450 using the proxy good method, and €3102 using the opportunity cost method [11]. In the same year, a study in Finland indicated that the medical costs of an AD patient were €23,059 per person per year [12]. Thus, AD creates a heavy burden to both patients’ families and society and is also a huge challenge to economic development and elderly healthcare.…”
Section: Introductionmentioning
confidence: 99%